The predictive value of total body PET/CT in high PD-L1 expression and immunotherapy in advanced non-small cell lung cancer patients - Jin, Huibin; Hu, Bingxin; Zhang, Jie; Long, Ye; Xuan, Ang; Wu, Xinyu; Xu, Junling; Gao, Yongju (Frontiers in Oncology, 2025)
IntroductionTotal-body positron emission tomography/computed tomography (PET/CT) using uEXPLORER scanners demonstrates superior imaging capabilities for assessing programmed death ligand 1 (PD-L1) expression heterogeneity between primary tumors (PTs) and metastatic tumors (MTs) in advanced nonsmall cell lung cancer (NSCLC). MethodsThis retrospective study of 99 treatment-naïve NSCLC patients revealed that metabolic parameters (SUVmax, SUR-L, and SUR-BP) derived from biopsy-correlated PET/CT sites significantly predicted high PD-L1 expression (TC ≥ 50% or IC ≥ 10% by IHC). ResultsSUR-L exhibited the highest diagnostic accuracy (AUC = 0.758, p < 0.001). Among 30 immunotherapytreated patients, PD-L1 positivity and SUR-BP ≥ 7.30 were associated with prolonged disease-free survival (DFS) (p = 0.012 and p = 0.035, respectively).DiscussionOur findings establish SUR-BP as a novel non-invasive biomarker for immunotherapy prognosis in NSCLC, addressing spatial heterogeneity challenges in PD-L1 assessment.